Psychosocial Impact of Adolescents with Juvenile Diabetes Long-Term At Al Nasiriya Diabetic and Endocrinology Center - Hussein, Adil Ali; Hatab, Khetam Mutasher (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Psychological and social problems can impair the individual’s or family’s ability to carry out diabetes care tasks and therefore potentially compromise health status. There are opportunities for the clinician to routinely assess psychosocial status in a timely and efficient manner for referral to appropriate services. A systematic review and metaanalysis showed that psychosocial interventions modestly but significantly improved A1C (standardized mean difference –0.29%) and mental health outcomes. However, there was a limited association between the effects on A1C and mental health, and no intervention characteristics predicted benefit on both outcomes. Objectives: To find out impact of juvenile diabetes long-term treatment upon adolescents’ psychosocial and to discovery out the relationship between impact of long-term treatment with adolescents specific demographic data. Methodology: A descriptive study design was performed to determine the psychosocial impact of juvenile diabetes long-treatment upon in Al Nasiriya diabetic and endocrinology center. The study had started from February 6th, 2019 to June 7th, 2019. Non – probability sample of (100) adolescents were selected. Conclusion: The present study concludes that fair impact of long-term treatment of diabetes on the adolescents psychosocial factors (psychological and social); in addition the statistical test shows that the significant association between the adolescents’ psychosocial factors and their number of insulin dose. While there is a non-significant association with the age of diagnosis.